THE IMPACT OF PLANTAR OSCILLATION ON SHOOTING ACCURACY: A PRE- AND POST-TEST ANALYSIS OF CENTER OF PRESSURE IN COMPETITIVE SHOOTERS - Singh, C. P. Singh; Pal, Amit (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study aimed to evaluate the impact of a targeted intervention on plantar oscillation in professional shooters, focusing on both medial-lateral and anterior-posterior foot movements. Thirty professional shooters participated in pre-and post-test assessments of foot oscillation using stabilometric measurements. Paired sample t-tests were conducted to compare oscillations in the left foot, right foot, and both feet combined before and after the intervention. Significant improvements were observed in medial-lateral oscillation for the right foot (p = 0.017) and both feet combined (p = 0.013), indicating enhanced lateral stability post-intervention. However, no significant changes were found in anterior-posterior movements for either foot (p > 0.05). These findings suggest that the intervention successfully improved lateral balance but had a limited impact on forward-backward stability. Future interventions should incorporate additional activities to target anterior-posterior control for improved overall postural stability in shooting performance.